The consequences of the culture aspect and the power distance in the execution of global strategies in multinational companies in Brazil - Campos, Robson Pinheiro Rodrigues de (2015)
One of the challenges presented by the current conjecture in Global Companies is to recognize and understand that the culture and levels in structure of the Power Distance in Organizations in different countries contribute, significantly, toward the failure or success of their strategies. The alignment between the implementation and execution of new strategies for projects intended for the success of the Organization as a whole, rather than as an individual part thereof, is an important step towards reducing the impacts of Power Distance (PDI) on the success of business strategies. A position at odds with this understanding by Companies creates boundaries that increase organizational chasms, also taking into consideration relevant aspects such as, FSAs (Firm-Specific Advantages) and CSAs (Country-Specific Advantages). It is also important that the Organizations based in countries or regions of low Power Distance (PDI) between its individuals be more flexible and prepared to ask and to hear the suggestions from Regional and Local Offices. Thus, the purpose of this study is to highlight the elements of effective strategy implementation considering the relevant aspects at all levels of global corporate culture that justify the influences of power distance when implementing new strategies and also to minimize the impacts of this internal business relationship. This study also recognizes that other corporate and cultural aspects are relevant for the success of business strategies so consider, for instance, the lack of alignment between global and regional/local organizations, the need for competent leadership resources, as well as the challenges that indicate the distance between the hierarchical levels ─ Headquarters and Regional Office ─ as some of the various causes that prevent the successful execution of global strategies. Finally, we show that the execution of the strategy cannot be treated as a construction solely created by the Headquarters or by only one Board and that it needs to be understood as a system aimed at interacting with the surroundings.